2012
DOI: 10.2174/13816128130309
|View full text |Cite
|
Sign up to set email alerts
|

Lysosomal Rerouting of Hsp70 Trafficking as a Potential Immune Activating Tool for Targeting Melanoma

Abstract: Tumor specific cell surface localization and release of the stress inducible heat shock protein 70 (Hsp70) stimulate the immune system against cancer cells. A key immune stimulatory function of tumor-derived Hsp70 has been exemplified with the murine melanoma cell model, B16 overexpressing exogenous Hsp70. Despite the therapeutic potential mechanism of Hsp70 transport to the surface and release remained poorly understood. We investigated principles of Hsp70 trafficking in B16 melanoma cells with low and high l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 33 publications
2
8
0
Order By: Relevance
“…Given that Hsp70 is frequently upregulated in tumour cells, where it is specifically present on the tumour cell surface, and that derailed endocytosis is a feature of cancer [8], we hypothesized that sHsp70 may have a general impact on the endocytic process. We previously showed that overexpression of Hsp70 in B16 mouse melanoma cells gave rise to the concentration of sHsp70 [9]. Here we show for the first time, using the B16 model and human A375 melanoma cells, that high levels of Hsp70 facilitate CIE even at unstressed conditions.…”
Section: Introductionsupporting
confidence: 51%
See 1 more Smart Citation
“…Given that Hsp70 is frequently upregulated in tumour cells, where it is specifically present on the tumour cell surface, and that derailed endocytosis is a feature of cancer [8], we hypothesized that sHsp70 may have a general impact on the endocytic process. We previously showed that overexpression of Hsp70 in B16 mouse melanoma cells gave rise to the concentration of sHsp70 [9]. Here we show for the first time, using the B16 model and human A375 melanoma cells, that high levels of Hsp70 facilitate CIE even at unstressed conditions.…”
Section: Introductionsupporting
confidence: 51%
“…To determine whether Hsp70 expression levels generally have an impact on the endocytic activity in unstressed cells, we used stably transfected tetracycline-inducible systems for Hsp70 overexpression in mouse B16 and human A375 melanoma cells (Hsp70) [9]. Cells stably transfected with empty vector served as control (ctrl).…”
Section: Resultsmentioning
confidence: 99%
“…Membrane alterations, signal pathways from membranes to hsp genes and Hsps themselves play fundamental roles in the aetiology of several human diseases, such as cancer or type 2 diabetes [6]. For therapeutical purposes the membrane lipid structure can be directly modified by a membrane-intercalating drug or by pharmacological modulation of enzymes involved in the metabolism of membrane lipids [5,6,[11][12][13]75,77,[140][141][142][143][144].…”
Section: Pharmacological and Nutritional Modulation Of Membranecontromentioning
confidence: 99%
“…In line with this study, we demonstrated that HIF-1α knockdown did not affect the hypoxia-induced reduction of Hsp70 membrane expression in MDA-MB-231 cells. A nonclassical pathway involving the endolysosomal system has been implicated in Hsp70 trafficking (Juhasz et al 2013;Mambula and Calderwood 2006;Gastpar et al 2005). Therefore, we hypothesize that hypoxia might reduce the Hsp70 membrane expression by directly modulating proteins involved in the regulation of the endolysosomal system (e.g., Rab proteins) leading either to a reduced transport to the membrane or an increased internalization.…”
Section: Discussionmentioning
confidence: 97%